S.A. Yesenin and N.V. Pokrovsky: on the History of Studying the Poet’s Reading Circle and his Ideas about Art - Svetlana A. Seregina (Studia Litterarum)
The article introduces a hitherto unaccounted source of Yesenin’s ideas about art — the work of N.V. Pokrovsky “Church archeology in connection with the history of Christian art” (Petrograd, 1916), which was in the poet’s personal library, in academic circulation. The essay examines the biographical circumstances that explain how Yesenin learned about this research and how he obtain it. The author of the article proves that traces of Yesenin’s acquaintance with Pokrovsky’s work are found in his treatise on art — “Keys of Mariya” (1918). She concludes that the poet’s ideas about the culture of Byzantium and the “baptized East” were formed, among other things, due to Pokrovsky’s research. The author proves that Yesenin’s image of a peasant hut as a symbolic temple goes back to Pokrovsky’s idea of a Russian traditional dwelling as the national architectural source of a tent temple. Pokrovsky’s description of the ornament of the Dmitrov Cathedral in Vladimir is considered as a direct source of the metaphorical comparison “ornament is music”, which opens the “Keys of Mariya.” It turns out that the important Yesenin’s idea to synthesize opposite types of art — visual and expressive — goes back, among other things, to the work of Pokrovsky.